The Mediating Role of Motivational Regulation on the Relationship of Emotional Intelligence with Physical Activity in Spanish Schoolchildren - Mikel Vaquero-Solís; Miguel Angel Tapia-Serrano; Pedro Antonio Sánchez-Miguel (MDPI AG, 2022)
The present study aimed to analyze the mediating role of different types of motivational regulations in the relationship established between emotional intelligence and physical activity. Participants were 431 secondary school students aged 12 to 16 years, 51.5% females (13.59 ± 1.03 years) and 48.5% males (13.50 ± 0.94 years), who completed a self-reported questionnaire of emotional intelligence, motivation and physical activity. The results showed a statistically significant positive association between emotional intelligence, physical activity, and more self-determined forms of motivation (intrinsic regulation, identified regulation and introjected regulation) (p < 0.05). Several mediation models were also presented that confirmed the mediating value of the more self-determined motivational regulations in the association established between emotional intelligence and physical activity, with the indirect effects being significant for intrinsic regulation, identified regulation, and introjected regulation (p < 0.05). Finally, we conclude on the importance of the management of emotions in order to propitiate a suitable motivational state that leads to physical activity. Therefore, this study highlights the importance of emotional intelligence for the practice of different forms of physical activity in young people.